Miles’ mechanism for generating surface water waves by wind, in finite water depth and subject to constant vorticity flow - Kern, N.; Chaubet, C.; Kraenkel, R. A. [UNESP]; Manna, M. A. (Elsevier, 2021)
The Miles’ theory of wave amplification by wind is extended to the case of finite depth h and a shear flow with (constant) vorticity Ω. Vorticity is characterised through the non-dimensional parameter ν=ΩU1/g, where g the gravitational acceleration, U1 a characteristic wind velocity. The notion of ’wave age’ is generalised to account for the effect of vorticity. Several widely used growth rates are derived analytically from the dispersion relation of the wind/water interface, and their dependence on both water depth and vorticity is derived and discussed. Vorticity is seen to shift the maximum wave age, similar to what was previously known to be the effect of water depth. At the same time, a novel effect arises and the growth coefficients, at identical wave age and depth, are shown to experience a net increase or decrease according to the shear gradient in the water flow.
Keywords: Constant vorticity; Finite depth; Miles theory; Wind wave growth rate; Wind-generated waves